STRUKTUR PERCAKAPAN PODCAST PADA CHANNEL YOUTUBE DEDDY CORBUZIER DALAM MENANGANI COVID-19 - Apreno, Reci (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The ability to speak in public in the digital era 4.0 is increasingly developing using digital media, one of which is podcasts. Podcasts have a different structure from other types of speaking discourse in general. For this reason, the purpose of this study is to describe the structure of podcast conversations on Deddy Corbuzier's youtube channel in dealing with covid-19. This study uses a qualitative approach with qualitative content analysis methods. The source of the data in this study is Deddy Corbuizer's podcast and the data in this study are all oral utterances that occur during the conversation process. Data collection using documentation techniques. The data analysis technique was carried out by content analysis techniques, namely data reduction, data presentation, and conclusion drawing. The results of this study found, speaking turns occur because of an understanding between the speaker and the speech partner in taking their turn to speak, pauses include short pauses and medium pauses, short pauses occur in the middle of speech marked by the phrase ehh and pauses are occurring at the end of the speech because there is no direct response. from the speech partner, overlapping speech occurs because of the speaking turn taking by the speech partner before the speaker gives the opportunity, backchannel occurs because of a response from the speech partner on the sidelines of the speaker's statement in the form of heem, he'eh, yes, okay, and pair Ajesensi is marked by the presence of questions asking how are you at the beginning of the conversation and thanks at the end of the conversation, in this case the questions and greetings already have automatic answers. This shows that in Deddy Corbuzier's podcast conversation there is a complete conversation structure. And has its own characteristics, especially in opening direct conversations to the point without too many introductions like other types of discourse